Ethical Challenges And Professional Skepticism In The Age Of Automated Auditing - Andi Hidayatul Fadlilah; Dwiyanjana Santyo Nugroho; Nelly Patria (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
The rapid advancement of artificial intelligence (AI) and automation technologies has reshaped the landscape of financial auditing, introducing both opportunities and ethical challenges. Automated auditing systems enhance efficiency, accuracy, and fraud detection, yet they also raise concerns about auditor independence, accountability, and the erosion of human judgment. This study examines how automation affects ethical decision-making and professional skepticism among auditors in technology-driven environments. Drawing on qualitative and quantitative insights, it explores issues such as algorithmic bias, data integrity, confidentiality, and the shifting roles of auditors in overseeing machine-generated evidence. The findings reveal that while automation improves analytical precision, it simultaneously challenges traditional ethical frameworks by blurring responsibility between human professionals and automated systems. To maintain trust and credibility in the auditing profession, auditors must balance technological reliance with critical thinking, ethical vigilance, and continuous professional development.